КЛАСТЕР МЕН ТЕРРИТОРИАЛДЫ-ӨНДІРІСТІК КЕШЕН ҰҒЫМДАРЫНЫҢ ЕРЕКШЕЛІКТЕРІ. (Journal of Economic Research & Business Administration, 2016)
In this article analyzed cluster’s theory, comme the importance factor of the development of the competitiveness ofthe national economics.